Transvaginal sonography and sonography 3D in women with endometrial hyperplasia - Chróściel, Mieczysław; Czekierdowski, Artur (Menopause Review/Przegląd Menopauzalny, 2008)
Aim: To assess correlation between endometrial thickness, Doppler blood flow indices and 3D in women with endometrial hyperplasia (EH) or endometrial cancer (EC). Material and methods: We studied a group of 80 women in whom 55 cases of EC and 25 cases of EH were found. In all cases a transvaginal 6-9 MHZ probe and a Kretz Voluson 730 (Austria) equipment were used. Clinical data such as menopausal status, age, were compared with tumor histological grade, FIGO stage and preoperative sonography. Sonographical criteria included endometrial thickness and volume, Doppler blood flow indices PI, RI and PSV studied in the uterine artery as well as 3D vascularity and blood flow indices VI, FI and VFI. Results: Endometrial thickness and volume were significantly different in groups with EH and EC (p=0.0004 and p=0.02, respectively). Menopausal status, histological grade and FIGO stage were correlated with endometrial thickness (p=0.02; p=0.03; p=0.04, respectively) but not with endometrial volume. Medians of VI FI i VFI were significantly different in both groups with EH and EC (p=0.009, p=0.05 and p=0.009, respectively). Menopausal status and clinical stage of EC were significantly correlated with VI: p=0.003; FI: p=0.02 VFI: p=0.03. Also, positive and significant correlations between 2D blod flow indices and 3D vascularity and flow indices were found (p>0.02). Conclusions: Doppler assessment of vascularity and flow may be used as additional criteria allowing for better preoperative discrimination of endometrial hyperplasia and cancer. Low risk of malignancy based of sonographic and sonoangiographic criteria could safely exclude some patients from invasive procedures such as unnecessary endometrial biopsy.